THE NUMERICAL ANALYSIS OF THE EXPERIMENTAL SCHEMES ON DETECTION OF COUPLE-STRESS EFFECTS UNDER STATIC AND DYNAMIC EXTERNAL FORCES - Korepanov, V.V. (Perm Federal Research Centre Journal, 2014)
The paper presents the historical aspects of the theory of Cosserat continuum and the main stages of its development. The features of the theory and main stages was considered and associated of the development of experimental schemes to detect the couple-stress effects on the basis of solving two- and three-dimensional problems in the context of the asymmetric elasticity theory. First results of such experiments raised a number of issues related to the corresponding mathematical problem and its experimental analogue. In this regard, there was a problem of a broad series of numerical investigations aimed at assessing the impact of various factors in the making of operative embodiment, loading scheme and the choice of material to the level of quantities measured in the experiment. Such investigations allow us to estimate the prospects of future experiments aimed to identification the facts of the couple-stress behavior of materials under static and dynamic external influences.